Interleukin-6 gene polymorphism in Saudi population with recurrent aphthous stomatitis - Samah Jameel Saeed Shabana; Muhammad Hamid Zaini Mutawakkil; Hassan Mamdouh Aly El-Ashmaoui; Fathya Mohammed Abdel-Qawi Zahran (Elsevier, 2021)
Introduction: Recurrent aphthous ulcers are common but poorly understood mucosal disorder. Local and systemic conditions, genetic, immunological, and microbial factors may play a role in the pathogenesis of recurrent aphthous ulceration (RAS). Different aetiologies and mechanisms might be involved in the aetiopathogenesis of aphthous ulceration. Cytokines are thought to play an important role and high levels of interleukin (IL)-6, a pro-inflammatory cytokine, have been detected in the circulation of ulcer tissue. The purpose of the present study was to investigate if polymorphisms of IL-6 gene are associated with RAS in a cohort of specific population. Methodology: A total of 37 RAS patients and 18 healthy controls were included in the study. The genotypes of IL-6 gene −174G/C polymorphisms were determined using polymerase chain reaction and sequencing. Results: Four SNPs were analyzed, one known mutation which been evaluated as a risk factor for RAS, and three new mutations were investigated. The genotype frequencies of −174G/C polymorphism showed no statistically significant differences between RAS patients and controls (p/ 0.629). Polymorphisms of Rs1800795 heterozygous genotype were found in 21.62% of cases, and 33.33% of controls. Homozygous mutant genotype was found in 5.41% of cases and no homozygous mutant genotype was found in control group. The normal alleles were found in 72.97% of cases and 66.67% of control. Conclusion: Thus, according to our study, IL-6 gene polymorphism is not involved in RAS pathogenesis. Further studies should be done on large sample size to detect any association with pathogenesis. However, an alternative reasoning could point out to a complex interactive effect on IL-6 expression that might exist between any of the detected polymorphisms.